2015
DOI: 10.1016/j.physbeh.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Ceftriaxone attenuates acquisition and facilitates extinction of cocaine-induced suppression of saccharin intake in C57BL/6J mice

Abstract: Growing evidence implicates glutamate homeostasis in a number of behaviors observed in addiction such as acquisition of drug taking, motivation, and reinstatement. To date, however, the role of glutamate homeostasis in the avoidance of natural rewards due to exposure to drugs of abuse has received little attention. The aim of the current study was to evaluate the beta-lactam antibiotic, ceftriaxone, which has been shown to normalize disrupted glutamate homeostasis associated with exposure to drugs of abuse, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
2
2
0
Order By: Relevance
“…Instead, we hypothesize that cocaine exposure induces long-lasting neuroplastic adaptations in the mesocorticolimbic system, responsible for natural reward processing, leading to the observed changes in saccharin preference. In line with this, previous studies have extensively documented that pairing cocaine with saccharin dramatically decreases saccharin intake 12 , 13 , 21 23 . This effect appears to be due to a decrease in the perceived value of saccharin as a reward, rather than an impairment in sweet taste sensitivity 13 .…”
Section: Discussionsupporting
confidence: 68%
“…Instead, we hypothesize that cocaine exposure induces long-lasting neuroplastic adaptations in the mesocorticolimbic system, responsible for natural reward processing, leading to the observed changes in saccharin preference. In line with this, previous studies have extensively documented that pairing cocaine with saccharin dramatically decreases saccharin intake 12 , 13 , 21 23 . This effect appears to be due to a decrease in the perceived value of saccharin as a reward, rather than an impairment in sweet taste sensitivity 13 .…”
Section: Discussionsupporting
confidence: 68%
“…Instead, we hypothesize that cocaine exposure induces long-lasting neuroplastic adaptations in the mesocorticolimbic system, responsible for natural reward processing, leading to the observed changes in saccharin preference. In line with this, previous studies have extensively documented that pairing cocaine with saccharin dramatically decreases saccharin intake 12,13,[21][22][23] . This effect appears to be due to a decrease in the perceived value of saccharin as a reward, rather than an impairment in sweet taste sensitivity 13 .…”
Section: Discussionsupporting
confidence: 64%
“…Thus, our results could indicate that mice exposed to repeated caffeine-mixed alcohol during adolescence may be at greater risk for future abuse of rewarding substances. To test this hypothesis, we investigated how repeated exposure to caffeine-mixed alcohol in adolescence would alter intake of a natural reward (saccharin) in adulthood [ 30 , 31 , 57 , 58 ]. In support of our hypothesis, we found that mice exposed to caffeine-mixed alcohol increased voluntary saccharin consumption and preference compared to water control mice ( Fig 7 ).…”
Section: Discussionmentioning
confidence: 99%